PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTI YANG TERDAFTAR DI BEI PADA TAHUN 2016-2020 - Serli Oktapiani; Sri Andriani; Khairunnisa Khairunnisa (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
A growing local epidemic that has caused a health crisis and disrupted economic growth, especially in Indonesia, the spread of COVID-19 has created a sudden and sharp drop in revenue for companies in many industries, one of which is the property sector, which has been severely affected, causing consumers and investors delay or wait for the situation to improve to make purchases in the property sector. The research objective is to examine the effect of capital structure (debt to equity ratio) and profitability (ratio on equity) on firm value (price earning ratio). The population consists of 65 companies, a sample of 14 property companies listed on the Indonesia Stock Exchange, using panel data regression analysis using the documentation method. The test results are obtained from software eviews 12. The results of the study are that the capital structure (DER) has a positive and significant effect on firm value. , profitability (ROE) has a negative and significant effect on firm value.